Water Purification Mechanism Using Appropriate Technology Reverse Osmosis, Ozonation, UV (Ultraviolet) Sterilization: Mekanisme Penjernihan Air Menggunakan Teknologi Tepat Guna Reverse Osmosis, Ozonasi, UV (Ultraviolet) Sterelisasi - Makida, Zilfiyatul; Sudarti, Sudarti (Media Ilmiah Teknik Lingkungan (MITL), 2025)
Global problems related to scarcity of clean water and water pollution have created an urgent need for effective solutions. Rapid urbanization and inexorable population growth have exacerbated this situation, increasing demand for clean water while decreasing its availability. In responding to this challenge, desalination technologies such as reverse osmosis (RO) and membrane processes have been considered as promising solutions although they are still faced with technological obstacles and large capital investments. In addition, concerns about water pollution by organic pollutants and bacteria have encouraged the development of effective wastewater treatment methods, including the use of conventional ozonation with membrane contactors and UV light. This research aims to explore new approaches to water treatment, including the use of membrane technology, conventional ozonation, and innovative disinfection methods such as UV light, with the hope of contributing to solving global problems related to clean water and water pollution. Through a series of comprehensive methodological steps, this research highlights the potential of these technologies to improve water quality and reduce contamination in a variety of application contexts.